Weak solutions to one initial-boundary value problem with three boundary conditions for quasilinear evolution equations of the third order - Faminskii, A.V.; Bashlykova, I.Yu. (Український математичний вісник, 2008)
Global well-posedness in a class of weak solutions is established to one initial-boundary value problem with three boundary conditions for a wide class of quasilinear dispersive evolution equations of the third order in the multidimensional case. The considered class of equations generalizes the Korteweg–de Vries, the Korteweg–de Vries–Burgers and the Zakharov–Kuznetsov equations.